2016
DOI: 10.1159/000447396
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Novel P2Y12 Inhibitors in Patients with Acute Myocardial Infarction: A Treatment Paradox

Abstract: Objective: To assess the real-world use, clinical outcomes, and adherence to novel P2Y12 inhibitors. Methods: We evaluated 1,093 consecutive acute myocardial infarction patients undergoing a percutaneous intervention. Patients were derived from a prospective, multicenter, nationwide registry and were followed for 30 days; 381 patients (35%) received clopidogrel, 468 (43%) received prasugrel, and 244 (22%) received ticagrelor. Patients treated with clopidogrel were older and more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…8,28 Moreover, patients who have the highest ischemic risk often receive the least aggressive treatment, including both invasive and medical management; a phenomenon that has been termed the "treatment-risk paradox." [29][30][31][32] Suboptimal treatment of patients with multiple ischemic risk factors was highlighted in the Pattern of Repeat Cardiovascular Events…”
Section: Suboptimal Treatment Of Patients With Nstemimentioning
confidence: 99%
See 2 more Smart Citations
“…8,28 Moreover, patients who have the highest ischemic risk often receive the least aggressive treatment, including both invasive and medical management; a phenomenon that has been termed the "treatment-risk paradox." [29][30][31][32] Suboptimal treatment of patients with multiple ischemic risk factors was highlighted in the Pattern of Repeat Cardiovascular Events…”
Section: Suboptimal Treatment Of Patients With Nstemimentioning
confidence: 99%
“…49 Patients with NSTEMI at high ischemic risk were also not treated optimally in the Myocardial Ischaemia National Audit Project (MINAP) registry, in which the use of guideline-indicated care for patients with NSTEMI decreased with increasing GRACE risk score, even though optimal guideline-indicated care was associated with greater survival gains for high-risk patients. 31 Adherence to guideline recommendations for the management of 51 Furthermore, data from national registries have indicated that patients with NSTEMI are more likely to receive clopidogrel than the potent P2Y 12 inhibitors, 29,52,53 which are generally preferentially recommended in international guidelines. 13,[15][16][17] There is also evidence to suggest that patients with NSTEMI may be less likely to be treated in academic medical centers than patients with STEMI, and therefore less likely to be directed to larger hospitals with catheterization laboratories; indicating some degree of referral bias toward patients with STEMI.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clopidogrel (300-600 mg loading dose, 75 mg daily dose) is recommended (Class I, LOE B) only for those patients who cannot receive ticagrelor or prasugrel or who require oral anticoagulation that may expose patients to an unacceptably high bleeding risk with prasugrel or ticagrelor (59). Despite these clear-cut recommendations, the utilisation of potent platelet inhibitors (prasugrel/ticagrelor) in the real world is still below its expectations (42,51,(60)(61)(62). Among other things, bleeding risk, treatment costs and issues with reimbursement in certain countries may explain this unexpected phenomenon.…”
Section: The Presentmentioning
confidence: 99%
“…Several other investigators have explored similar issues regarding the contemporary selection of antiplatelet therapy. 8 Perhaps the most important finding of this study was that prasugrel was used in 34% of ACS patients with a documented contraindication (history of stroke or transient ischemic accident, age >75 years, and body weight <60 kg). The selection of newer P2Y 12 inhibitors may be even more complex in European countries.…”
mentioning
confidence: 78%